From cranial nerve palsy to seizures—All the signs that lead to secondary Fahr's syndrome. Issue 5 (5th May 2021) - Pereira, Gabriela Sobreira; Ferreira, Ana; Castro, Laura; Fernandes, Magda; Cotter, Jorge
Abstract: Neuroimaging scan and calcium/phosphorus metabolism evaluation should be considered in patients with new onset of neuropsychiatric symptoms, to provide an earliest detection of pathological and metabolic alterations, such as Fahr's syndrome. Abstract : Neuroimaging scan and calcium/phosphorus metabolism evaluation should be considered in patients with new onset of neuropsychiatric symptoms, to provide an earliest detection of pathological and metabolic alterations, such as Fahr's syndrome.